Comparison of Misoprostol and Mefenamic Acid on Reducing Menstrual Bleeding in Patients Suffering From Heavy Menstrual Bleeding - Tahereh Eftekhar; Marjan Ghaemi; Aref Abedi; Mahboobeh Shirazi (Tehran University of Medical Sciences, 2019)
Objective: Heavy menstrual bleeding is one of the most frequent complaints of women. Various therapeutic approaches have been applied to treat this condition. In this study, we compared the efficacy of mefenamic acid and misoprostol in reducing menorrhagia. Materials and methods: This is a randomized clinical trial study performed on 60 patients with menorrhagia. They were divided into two equal groups and randomly received mefenamic acid or misoprostol. Cycle duration, bleeding volume (according to the pictorial blood assessment chart), hemoglobin, hematocrit, and pad count were recorded before and after treatment. Side effects of treatment regimens were recorded. Results: Blood loss volume per menstruation day in the mefenamic acid group was 118.40 ± 36.26 ml before treatment which decreased to 48.50 ± 24.71 ml after treatment (p = 0.262). Misoprostol reduced menstrual bleeding volume from 135.37 ± 34.85 ml per day to 49.40 ± 32.161 ml (p = 0.003). Mean duration of the menstrual period in patients receiveding mefenamic acid was 9.50 ± 3.27 days which decreased to 7.73 ± 2.14 days after treatment (p = 0.001). The similar change occurred in the misoprostol group and the mean duration of the menstrual period decreased from 7.70 ± 2.10 to 6.37 ± 2.29 days (p = 0.002). The number of pads used by patients in the mefenamic acid group before treatment was 23.20 ± 12.61 which was decreased to 14.33 ± 5.86 after treatment (p = 0.001). This alteration in misoprostol group was from 20.67 ± 6.12 to 15.53 ± 6.49 (p = 0.001). Conclusion: Misoprostol can significantly reduce menstrual bleeding.